1999
DOI: 10.1180/002646199548961
|View full text |Cite
|
Sign up to set email alerts
|

Carbon isotope ratios and nitrogen abundances in relation to cathodoluminescence characteristics for some diamonds from the Kaapvaal Province, S. Africa

Abstract: Secondary ion mass spectrometry (SIMS) techniques have been used to study the variation of C isotope ratio and N abundance within selected diamonds in relation to their crystal growth zones. The growth zones are seen in cathodoluminescence (CL), and include both octahedral and cuboid zones within typical diamonds of external octahedral morphology. Compositions were determined by use of a primary 133Cs + ion beam and measurement of 12C-, 13C , and 12C14N-secondary ions at high mass resolution on a Cameca ims-4f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(56 citation statements)
references
References 43 publications
(97 reference statements)
7
47
1
1
Order By: Relevance
“…The carbon isotopes of the studied diamonds from three localities in China are thus interpreted to reflect the isotopic signature of their mantle source. Between core areas and outer growth zones within individual diamond or among separate diamonds, there are no correlations between the intensity of cathode luminescence and carbon isotope ratios, in accordance with the results of previous studies [19,38,39].…”
Section: Growth Zones Of Diamonds and Their Relationship To Carbon Issupporting
confidence: 81%
See 1 more Smart Citation
“…The carbon isotopes of the studied diamonds from three localities in China are thus interpreted to reflect the isotopic signature of their mantle source. Between core areas and outer growth zones within individual diamond or among separate diamonds, there are no correlations between the intensity of cathode luminescence and carbon isotope ratios, in accordance with the results of previous studies [19,38,39].…”
Section: Growth Zones Of Diamonds and Their Relationship To Carbon Issupporting
confidence: 81%
“…In-situ analyses with SIMS indicated that carbon isotopes in diamond depict complex growth zones. Moreover, complicated relations exist between carbon isotopes and nitrogen content as well as nitrogen isotopes in different occurrences [14][15][16][17][18][19][20][21][22].…”
mentioning
confidence: 99%
“…Ion microprobe studies of diamonds show variations from <100 ppm to >1000 ppm in very narrow growth zones in lithospheric diamonds (e.g. Harte et al, 1999a). Likewise, ion microprobe studies on LM diamonds show that substantial smallscale variations can occur within single diamonds; Hutchison et al (1999) record a variation from 0.1 to 260 ppm.…”
Section: Diamond Characteristicsmentioning
confidence: 99%
“…For the EIMF measurements, the "synAT" standard (a synthetic "A" diamond crystal, partial slice "T") was used [43]. The characteristics of this reference material are: 230.4 ppm N (wt) and δ 13 C PDB of −23.92 as determined by combustion analysis using a gas source mass spectrometer (analysed by S.R.…”
Section: Samples and Methodsmentioning
confidence: 99%